Pengaruh Likuiditas, Leverage, Aktivitas dan Pertumbuhan Penjualan Terhadap Profitabilitas - Vania Vania; Rosmiati Tarmizi (Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to analyze and obtain empirical evidence about the effect of from liquidity, leverage, activity, sales growth to profitability, (study of in automotive companies listed on the Indonesia stock exchange in 2018-2020). Research has 4 independent/independent variables were tested, namely: current ratio (CR), debt to equity ratio (DER), total asset turnover (TATO), sales growth, as well as 1 dependent/tested variable tested, namely : return on assets (ROA). The research population, namely: all automotive companies, so that There are 14 companies registered at idx.co.id. Sampling method used namely: purposive sampling can obtain 13 sample companies. Data analysis technique: multiple linear regression using SPSSver.17 application. This research has the following results: the following, liquidity and activity have a significant positive effect, sales growth the positive effect is not significant, while for leverage the negative effect is not significant impact on profitability, in automotive companies listed on the Indonesian stock exchange period 2018-2020.